IMPLEMENTASI PENILAIAN AFEKTIF PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA NEGERI 1 PARIANGAN - Adri Jumeldi (IAIN Batusangkar, 2016)
In this qualitative research, the researcher analyzed the implementation of affective assessment for Islamic education in high school 1 Pariangan. The interview, observation and documentation were used in collecting data. The result obtained indicate that the implemention of affective assessment for Islamic education was run well. It was marked by making lesson plan and making instrument of affective assessment and also giving appropriate score of students’ affective in instructional process. Teacher of Islamic education in high school 1 Pariangan has begun affective assessment by making the grating assessment. Teacher used observation sheet to measure spiritual and social behavior of students. Affective assessment through observation was done by the teacher when the students did group discussion in instructional process.Key words: Affective Assessment, Islamic Education, High School, Pariangan